2022
DOI: 10.1123/ijspp.2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilateral Dorsolateral Prefrontal Cortex High-Definition Transcranial Direct-Current Stimulation on Physiological and Performance Responses at Severe-Intensity Exercise Domain in Elite Road Cyclists

Abstract: Purpose: To investigate the effects of bilateral dorsolateral prefrontal cortex high-definition transcranial direct-current stimulation (HD-tDCS) on physiological and performance responses during exercise at the upper limit of the severe-intensity exercise domain in elite-level road cyclists. Methods: Eleven elite-level road cyclists (VO2peak: 71.8 [3.1] mL·kg−1·min−1) underwent the HD-tDCS or SHAM condition in a double-blind, counterbalanced, and randomized order. After 20 minutes of receiving either HD-tDCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Sample sizes of included studies ranged from 8 to 36 participants (13.6 ± 6.6). Athletes were experienced in various sports disciplines: cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42], bodybuilding [31], resistance training [38], basketball [40], parkour [3], taekwondo [17, 32] and pistol-shooting [33]. Additionally, some studies reported that athletes competed at the regional [39], national [17, 32, 37, 42, 43] and/or international level [17, 30, 32, 37].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample sizes of included studies ranged from 8 to 36 participants (13.6 ± 6.6). Athletes were experienced in various sports disciplines: cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42], bodybuilding [31], resistance training [38], basketball [40], parkour [3], taekwondo [17, 32] and pistol-shooting [33]. Additionally, some studies reported that athletes competed at the regional [39], national [17, 32, 37, 42, 43] and/or international level [17, 30, 32, 37].…”
Section: Resultsmentioning
confidence: 99%
“…For an overview of investigated sport-specific motor performances in each study, please see Table 1. Sport disciplines were categorized in the following performance domains: endurance (cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42]), strength (bodybuilding [31], resistance training [38]) & visuomotor skill (basketball [40], parkour [3], taekwondo [17, 32], pistol-shooting [33]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations